Partnering capacities for inclusive development in food provisioning. (12th July 2020) - Vellema, Sietze; Schouten, Greetje; Van Tulder, Rob
Abstract: Context: This article focuses on partnerships working on inclusive development and food security in agri‐food chains and agribusiness clusters that may feature institutional arrangements reinforcing inequality or inducing exclusion. Research question: The article develops a theory‐driven capacity framework for investigating how intervention strategies related to partnering generate developmental outcomes. Methods: Building on action–research and drawing on complementary literature streams, the framework distinguishes four specific capacities that individually and in configuration contribute to processes of inclusive development triggered by partnering processes. The framework is applied to two case examples targeting inclusive development in agri‐food chains and agribusiness clusters in domestic food markets in Benin and Nigeria. Results: Four capacities that enable partnerships to contribute to inclusive development are distinguished: deliberative, alignment, transformative and fitting capacity. Processes of inclusive development emerge from mobilizing and combining these complementary capacities. Capacities emerging in evolving joint actions, negotiations and deliberations in partnering processes generate developmental outcomes, which are not self‐evident results of partnerships. Presence of the four capacities propels the partnership's influence on transforming the terms of inclusion for specific groups. Policy implications: The differentiation of specific capacities embedded in partnering processes contrasts with generic partnership formulas focusing on the formalized and organizational features of partnerships and emphasizing sharing of resources and inputs. For partnerships to make a development impact, new capacities need to be developed and mobilized. This underscores the importance of skilful and experienced facilitators.